Ramadan Fasting and Maternal and Fetal Outcomes in Pregnant Women with Diabetes Mellitus: Literature Review - Kumar, Shejil; Diamond, Terrence (Frontiers in Endocrinology, 2022)
There is an emerging Muslim and diabetic population in the United States and other Western countries and majority of pregnant women and patients with diabetes mellitus choose to fast during Ramadan. Fasting during Ramadan in pregnant women with diabetes may represent a ‘perfect storm’ of metabolic disturbances including hyperglycemia, hypoglycemia and ketosis. Recent continuous and flash glucose monitoring data suggests increased glycemic variability (fasting hypo- and post-Iftar hyperglycemia) in non-pregnant patients with diabetes during Ramadan. Only five small-scale studies, predominantly focused on women with gestational diabetes mellitus in Muslim-majority nations have explored maternal glycemic outcomes during Ramadan which is associated with lower mean blood glucose levels and higher frequency of fasting hypoglycemia. Data is limited however on important clinical outcomes such as symptomatic and serious hypoglycemia requiring hospitalization. Results have been conflicting regarding maternal Ramadan fasting and association with fetal outcomes in women without diabetes. Only one recently published study reported on perinatal outcomes in pregnant women with gestational diabetes which found no effect of Ramadan exposure on mean birthweight or macrosomia frequency but lower neonatal hypoglycemia prevalence, however a significant limitation was lack of documentation of maternal fasting status. At this stage, due to paucity of data, the current medical recommendation is against Ramadan fasting for pregnant Muslim women with diabetes. Large-scale population-based studies are warranted regarding maternal and fetal outcomes in pregnant fasting women with diabetes and such studies should characterize maternal fasting status and have meaningful and consistent clinical outcomes. High-quality data derived from these studies can assist clinicians in providing more evidence-based advice to safely navigate both mother and fetus through a potentially challenging pregnancy.